173k views
1 vote
9x-6y=-42 simplified???

User Lsilva
by
5.3k points

2 Answers

2 votes

Answer: x = -4.666666667 + -0.6666666667y

Explanation:

Simplifying

9x + 6y = -42

Solving

9x + 6y = -42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6y' to each side of the equation.

9x + 6y + -6y = -42 + -6y

Combine like terms: 6y + -6y = 0

9x + 0 = -42 + -6y

9x = -42 + -6y

Divide each side by '9'.

x = -4.666666667 + -0.6666666667y

Simplifying

x = -4.666666667 + -0.6666666667y

User Dinesh Reddy Alla
by
5.6k points
2 votes

Answer:x = 4.666666667 + -0.6666666667y i think

Explanation:

User Alex Okrushko
by
5.0k points